Determinants of User Growth in B2C E-Commerce Platforms in South Africa - Viljoen-Nel, Liesl (University of the Witwatersrand, Johannesburg, 2024)
Globally, e-commerce has grown exponentially, especially during the COVID-19 pandemic, since people were forced to stay at home and shop online. South Africa has also experienced e-commerce growth, and the e-commerce penetration rate is forecasted to accelerate from 27 million registered e- commerce users in 2022 (43.5%) to 39.7 million registered e-commerce users by 2027 (64%). These statistics show that retailers will need targeted activities to ensure user growth in their e-commerce platforms since the competition between retailers to obtain e-commerce customers will intensify as it becomes a dominant sales channel in South Africa. This exploratory study investigated the "Determinants of User Growth in business-to-consumer (B2C) e-Commerce Platforms in South Africa" through the unique application of an academic (UTAUT2) and a practitioner model (AARRR). This study is the first South African study on e-commerce user growth. It is exclusive as existing literature mainly studies behavioural intention to use and use behaviour of information systems. However, it fails to address user growth, a critical component of information systems' retention and continuous use intention. This aim of this study was to understand the factors that impact use behaviour from a consumer perspective and, ultimately, user growth on e- commerce platforms in the fast-moving consumer goods industry specific to South Africa. A quantitative survey was conducted through a non-probability convenience sampling process from March to July 2023. Electronic survey links were distributed via e-mails, social media posts and online messaging services to reach a sample frame of 7,386 prospective respondents. Completed questionnaires were received from 743 respondents. After a data cleansing and rescaling procedure, the data from 550 respondents were analysed in a phased approach using exploratory factor, regression, correlation and moderation analyses. ii The independent variables accounted for 65.12% of the total variance in the UTAUT2 model, and performance expectancy and facilitating conditions emerged as the strongest predictors of behavioural intention. Neither age, gender, nor experience had a moderating impact on the independent variables and behavioural intention. Behavioural intention, however, significantly influenced user growth, as the customer transitioned from activation to retention to referral and the revenue phases of the user growth construct. Retention was the dominant factor in the user growth construct, explaining 18.66% of the total variance in the data. Revenue showed the highest correlation with behavioural intention, demonstrating that consumers will use a platform if they benefit from the transaction. Customer satisfaction moderated the relationship between behavioural intention and user growth, and facilitating conditions and user growth. This result demonstrates that customer service and support are instrumental in promoting user growth in B2C e-commerce platforms. South African customers have adopted B2C e-commerce platforms and have transitioned from the acquisition to the retention phases of the customer life cycle. However, shopping online in South Africa has not become a habitual activity or a necessity, which could be attributed to the availability of plenty of shopping malls with brick-and-mortar retailers throughout the country. It is recommended that retailers use data-driven insights to design targeted marketing activities for each phase of the purchase life cycle to strengthen behavioural intention and trigger user growth in B2C e-commerce platforms. The study makes a meaningful contribution to the South African digital commerce literature by concluding with practical recommendations that managers can apply to designing, implementing, and managing B2C e-commerce platforms in the fast-moving consumer goods or other consumer packaged goods industries.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: AARRR; e-commerce user growth; e-commerce adoption; e-commerce retention; e-commerce customer satisfaction; FMCG; UTAUT2; UCTD; SDG-8: Decent work and economic growth